Motivation, Cost, Risk: Research on the Value Perception of Study Tourism Products from the Perspective of Parents - Wen Tong; Li Simin; Su Haiyang; Xiao Kaijie (Redai dili, 2022)
Under the guidance of national education policy, the demand for study tourism has increased significantly, and it is worth paying attention to how parents, as the actual purchasing decision-makers of study tourism products, reflect their needs and attitudes. Taking nature education study tourism as the specific research context, questionnaires were distributed to parents of primary and secondary school students to investigate the causal relationship between study tourism motivation and value perception from the perspective of parents' perception and incorporated cost perception and risk perception into the research to analyze the internal mechanism and boundary conditions between study tourism motivation and value perception. A statistical analysis of data from 539 parents revealed that parents' perception of study tourism motivation significantly and positively affects value perception. Cost perception has a mediator role between study tourism motivation and value perception, and parents' perception of study tourism motivation has a positive impact on value perception through the path of weakening cost perception. Moreover, risk perception negatively affects value perception, but a positive effect was observed when exploring risk perception's interaction with study tourism motivation and cost perception, respectively. Risk perception significantly enhances the positive effect of study tourism motivation on value perception, while suppressing the negative effect of cost perception on risk perception. Specifically, compared to low-risk perceptions, parents with high-risk perceptions perceive a more significant positive effect of study tourism motivation on value perception and a lower negative effect of cost perception on value perception; that is, risk perception plays a moderating role in the relationship between tourism motivation and value perception and in the path of the relationship between cost perception and value perception. However, when risk perception reaches a high level, its moderating effect on the relationship between cost perception and value perception is not significant; that is, parents pay more attention to risk and safety issues than to cost issues. The main theoretical contribution of this study is that it forms a theoretical complement to the investigation of the relationship between motivation and value, thus revealing the importance of the value of education for the average non-only-child family in China and cost as an important consideration for such families in their educational investment. It verifies the positive role of risk perception in the context of study tourism, which promotes further understanding of risk in the academic community and enriches the theoretical research on study tourism. In addition, this study provides a valuable empirical basis and practical enlightenment for the development of study tourism. It is necessary to design study tourism products based on demand, highlight product value, increase publicity and marketing efforts, control the safety of activities, set reasonable prices, and gain the attention of parent groups, all of which will be important considerations in further expanding the study tourism market.